Transcription Factor ADS-4 Regulates Adaptive Responses and Resistance to Antifungal Azole Stress - Wang, Kangji (Antimicrob Agents Chemother, 2015)
Azoles are commonly used as antifungal drugs or pesticides to control fungal infections in medicine and agriculture. Fungi adapt to azole stress by rapidly activating the transcription of a number of genes, and transcriptional increases in some azole-responsive genes can elevate azole resistance. The regulatory mechanisms that control transcriptional responses to azole stress in filamentous fungi are not well understood. This study identified a bZIP transcription factor, ADS-4 (antifungal drug sensitive-4), as a new regulator of adaptive responses and resistance to antifungal azoles. Transcription of ads-4 in Neurospora crassa cells increased when they were subjected to ketoconazole treatment, whereas the deletion of ads-4 resulted in hypersensitivity to ketoconazole and fluconazole. In contrast, the overexpression of ads-4 increased resistance to fluconazole and ketoconazole in N. crassa. Transcriptome sequencing (RNA-seq) analysis, followed by quantitative reverse transcription (qRT)-PCR confirmation, showed that ADS-4 positively regulated the transcriptional responses of at least six genes to ketoconazole stress in N. crassa. The gene products of four ADS-4-regulated genes are known contributors to azole resistance, including the major efflux pump CDR4 (Pdr5p ortholog), an ABC multidrug transporter (NcAbcB), sterol C-22 desaturase (ERG5), and a lipid transporter (NcRTA2) that is involved in calcineurin-mediated azole resistance. Deletion of the ads-4-homologous gene Afads-4 in Aspergillus fumigatus caused hypersensitivity to itraconazole and ketoconazole, which suggested that ADS-4 is a functionally conserved regulator of adaptive responses to azoles. This study provides important information on a new azole resistance factor that could be targeted by a new range of antifungal pesticides and drugs.